NEW RANKING METHOD OF TRAFFIC NOISE REDUCTION MEASURES - Shevchenko, Yulia (Proceedings of National Aviation University (archive), 2013)
<!--[if gte mso 9]> 1024x768 <![endif]-->The paper presents new ranking method of traffic noise reduction measures. Mathematical model for simultaneous estimation of different noise reduction methods for multiple locations was developed. For realization of the proposed model empirical dependencies for effective time for vehicles of different categories were obtained on the base of series of experimental studies<!--[if gte mso 9]> Normal 0 false false false <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->